'Mopping up tears in the academy' – working-class academics, belonging, and the necessity for emotional labour in UK academia. Issue 1 (2nd January 2021) - Rickett, Bridgette; Morris, Anna
ABSTRACT: Previous research exploring how working-class women experience UK Higher Education (HE) work has made evident recurring themes around social segregation and corresponding difficulties with feeling they belong. This paper develops this work by exploring the ways in which UK, HE based working-class women lecturers talk about their sense of belonging. It was found that, in contemporary UK HE, lecturing work is located within a marketised space where caring for students is central and the deployment of emotional labour to seen to be a necessary requirement to meet those demands. In addition, this labour is understood to be work that working-class women can readily take up, and as one of the few vehicles to enable feelings of value and belonging. However, this work is also devalued, unaccounted for and potentially harmful to those who do engage in it, therefore shoring up/ reinforcing a class and gender stratified UK academy.